2021
DOI: 10.3390/cancers13030381
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Repair and Chromatin Crosstalk in Cancer Therapy

Abstract: Aberrant DNA repair pathways that underlie developmental diseases and cancers are potential targets for therapeutic intervention. Targeting DNA repair signal effectors, modulators and checkpoint proteins, and utilizing the synthetic lethality phenomena has led to seminal discoveries. Efforts to efficiently translate the basic findings to the clinic are currently underway. Chromatin modulation is an integral part of DNA repair cascades and an emerging field of investigation. Here, we discuss some of the key adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…In addition to its functional role in the nucleosome to ensure genomic stability, ( γ )H2A.X has a specialized cellular function by signaling and initializing DNA repair [ 47 , 62 , 63 ]. The H2A.X phosphorylation is considered one of the first reactions in the cellular DDR, particularly to DNA DSBs, which are among the DNA lesions with the most pronounced cytotoxicity [ 64 , 65 ].…”
Section: Histone γ H2axmentioning
confidence: 99%
“…In addition to its functional role in the nucleosome to ensure genomic stability, ( γ )H2A.X has a specialized cellular function by signaling and initializing DNA repair [ 47 , 62 , 63 ]. The H2A.X phosphorylation is considered one of the first reactions in the cellular DDR, particularly to DNA DSBs, which are among the DNA lesions with the most pronounced cytotoxicity [ 64 , 65 ].…”
Section: Histone γ H2axmentioning
confidence: 99%
“…It found that olaparib improved rPFS and objective response rate in comparison to treatment with enzalutamide or abiraterone, although concluded that further studies are required to better define the genetic mutations that will sensitize a cancer to olaparib. For patients with PCa and at least one alteration in BRCA1, BRCA2 or ATM (a serine threonine kinase involved in the processing of DSBs and in HRR) ( 90 , 91 ), overall survival was significantly longer for patients that received olaparib ( 79 ). However, analysis from the TRITON2 study of PARP inhibition with rucaparib found that of the 49 patients with mCRPC identified to have ATM mutation, only 4.1% showed a significant decline in PSA following treatment ( 92 ).…”
Section: Immunotherapies and Dna Repair Targeted Therapies: Precision...mentioning
confidence: 99%